Efficacy of Ultrasound-Guided Serratus Anterior Plane Block for Postoperative Analgesia in Patients Undergoing Breast Surgery: A Systematic Review and Meta-Analysis of Randomised Controlled Trials - Nian-Qiang Hu; Qi-Qi He; Lu Qian; Ji-Hong Zhu (Pain Research and Management)
Objective. Serratus anterior plane block (SAPB) provides effective thoracic analgesia. This systematic review and meta-analysis was conducted to assess the safety and efficacy of SAPB for postoperative analgesia after breast surgery. Methods. A systematic literature search was performed using Embase, PubMed, Web of Science, and the Cochrane Library for eligible randomised controlled trials. The primary outcomes involved the administration of intraoperative and postoperative opioids. The Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach was used for rating the quality of evidence for making recommendations. Results. Overall, 13 studies comprising 826 patients met the inclusion criteria (412 in the SAPB group and 414 in the control group). Patients treated with SAPB exhibited a significantly lower postoperative opioid consumption (mean difference, −38.51 mg of oral morphine equivalent; 95% confidence interval (CI), −60.97 to −16.05; P<0.01; I2 = 100%), whereas no difference was observed in the intraoperative opioid consumption (mean difference, −9.85 mg of oral morphine equivalent; 95% CI, −19.52 to −0.18; P=0.05; I2 = 94%). In addition, SAPB significantly decreased the occurrence of postoperative nausea and vomiting (risk ratio, 0.32; 95% CI, 0.19–0.55; P<0.05;I2 = 38%) and reduced pain scores during the postoperative period (1 h: standardised mean difference (SMD), −1.23; 95% CI, −2.00 to −0.45; I2 = 92%; 2 h: SMD, −0.71; 95% CI, −1.00 to −0.41; I2 = 48%; 4 h: SMD, −1.52; 95% CI, −2.77 to −0.27; I2 = 95%; 6 h: SMD, −0.80; 95% CI, −1.51 to −0.08; I2 = 81%; 8 h: SMD, −1.12; 95% CI, −1.98 to −0.27; I2 = 92%; 12 h: SMD, −0.78; 95% CI, −1.21 to −0.35; I2 = 83%; and 24 h: SMD, −0.71; 95% CI, −1.20 to −0.23; I2 = 87%; P<0.05 for all). Conclusion. SAPB was safe and effective after breast surgery to relieve postsurgical pain. However, additional well-developed trials are required to validate these findings.